2000
DOI: 10.1001/archinte.160.10.1417
|View full text |Cite
|
Sign up to set email alerts
|

Charges for Medical Care at Different Hospitals

Abstract: Charges for the same hospital service vary substantially. Greater visibility might reduce some variation by bringing outliers into closer scrutiny. Patients seeking care and paying out-of-pocket could save financially by comparison shopping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In a 1997 letter to the editor in the British Medical Journal , the authors reported on their small investigation of 62 chemist shops in Bath, U.K., in which they found that the price charged for a month's supply of donepezil (Aricept; Eisai Inc, Woodcliff Lake, NJ) ranged from £68 to £120, and in general they found lower prices quoted by chemists that were not part of a chain ( Jones, Mann, and Saunders 1997). More recently, Redelmeier et al (2000) surveyed 66 hospitals from every large city in the United States and Canada and documented variation in hospital charges to individuals paying out of pocket; the price to an uninsured patient for filling a prescription for fluoxetine varied fourfold among hospital pharmacies, ranging from $26 to $93.…”
Section: Discussionmentioning
confidence: 99%
“…In a 1997 letter to the editor in the British Medical Journal , the authors reported on their small investigation of 62 chemist shops in Bath, U.K., in which they found that the price charged for a month's supply of donepezil (Aricept; Eisai Inc, Woodcliff Lake, NJ) ranged from £68 to £120, and in general they found lower prices quoted by chemists that were not part of a chain ( Jones, Mann, and Saunders 1997). More recently, Redelmeier et al (2000) surveyed 66 hospitals from every large city in the United States and Canada and documented variation in hospital charges to individuals paying out of pocket; the price to an uninsured patient for filling a prescription for fluoxetine varied fourfold among hospital pharmacies, ranging from $26 to $93.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work using a similar methodology measured variation in charges for elective hospital procedures and generic prescription drugs. An overall coefficient of variation of 0.53 was reported across hospitals in the United States and Canada for prices of selected therapeutic services and a coefficient of variation of 0.16 was reported across pharmacies in Canada for prices of selected generic medications [7], [8]. Our calculated coefficient of variation for Ontario cataract surgeons suggests that the variability in price for a specialty lens is similar to other therapeutic services, but much greater than the variability in generic drug prices.…”
Section: Discussionmentioning
confidence: 71%
“…10,27 Charges, which vary considerably for the same hospital service, are occasionally made transparent to clinicians because patients receive billed charges and may make providers aware of them. 16,28 The actual cost of services and reimbursements, however, are rarely revealed. In fact, they may be kept as proprietary information that cannot be disclosed under civil and/or criminal penalty.…”
Section: Figurementioning
confidence: 99%